Legal Certainty in the Legislative System in Indonesia study on the Information and Electronic Transactions Law - Hempi Wanty Saragih; Abdul Rahman Maulana Siregar (Yayasan Multidimensi Kreatif, 2024)
Legal certainty is a fundamental element in the legal system that aims to create justice, order, and predictability in society. However, in practice, the existence of the Electronic Information and Transaction Law (UU ITE) often causes polemics due to multiple interpretations and inconsistent application. This study aims to examine the aspects of legal certainty in the ITE Law by highlighting articles that are in the public spotlight, such as related to insult and defamation, as well as their technical implementation in the field. The research method used is juridical-normative with an analytical approach to the text of the law and juridical-empirical through case studies and interviews with legal practitioners. The results of the study show that legal uncertainty in the ITE Law is caused by the lack of harmonization between the ITE Law and other laws, weak public understanding of regulations, and uneven implementation by law enforcement officials. To create better legal certainty, revisions to articles with multiple interpretations, capacity building for law enforcement officials, and comprehensive public education about the ITE Law are needed. This research is expected to make a theoretical contribution to the development of legal studies in Indonesia as well as a basis for recommendations for policymakers in improving the quality of legislation.